2016
DOI: 10.1016/j.icarus.2015.11.035
|View full text |Cite
|
Sign up to set email alerts
|

The electrical properties of Titan’s surface at the Huygens landing site measured with the PWA–HASI Mutual Impedance Probe. New approach and new findings

Abstract: Ten years after the successful landing of the Huygens Probe on the surface of Titan, we reassess the derivation of ground complex permittivity using the PWA-MIP/HASI measurements (Permittivity, Waves and Altimetry-Mutual Impedance Probe/Huygens Atmospheric Structure Instrument) at the frequencies 45, 90 and 360 Hz. For this purpose, we have developed a numerical method, namely "the capacity-influence matrix method", able to account for new insights on the Huygens probe attitude at its final resting position. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…Analyses of measurements taken by the Huygens Probe and assessment of its behavior upon landing indicate that the surface at the Huygens landing site was fine grained, relatively soft, and possibly covered in a 7 mm thick “fluffy” layer [ Zarnecki et al , ; Lorenz , ; Karkoschka et al , ; Atkinson et al , ; Schröder et al , ]. The surface also contained volatiles as indicated by the increase in abundance of CH 4 after the Huygens Probe landed, most likely resulting from the heating of liquid CH 4 that was present on the surface [ Niemann et al , , ], attenuation of acoustic signals after landing [ Lorenz et al , ], a change in the PWA‐MIP observations 11 min after landing [ Hamelin et al , ], and modeling of DISR spectra [ Rannou et al , ]. Located in a dry region of Titan, Williams et al [] interpret the moisture detected at the Huygens landing site as evidence of a recent local precipitation event or the result of recharging from a precipitation event located farther away because the surface should dry relatively rapidly.…”
Section: Connection With the Surfacementioning
confidence: 99%
“…Analyses of measurements taken by the Huygens Probe and assessment of its behavior upon landing indicate that the surface at the Huygens landing site was fine grained, relatively soft, and possibly covered in a 7 mm thick “fluffy” layer [ Zarnecki et al , ; Lorenz , ; Karkoschka et al , ; Atkinson et al , ; Schröder et al , ]. The surface also contained volatiles as indicated by the increase in abundance of CH 4 after the Huygens Probe landed, most likely resulting from the heating of liquid CH 4 that was present on the surface [ Niemann et al , , ], attenuation of acoustic signals after landing [ Lorenz et al , ], a change in the PWA‐MIP observations 11 min after landing [ Hamelin et al , ], and modeling of DISR spectra [ Rannou et al , ]. Located in a dry region of Titan, Williams et al [] interpret the moisture detected at the Huygens landing site as evidence of a recent local precipitation event or the result of recharging from a precipitation event located farther away because the surface should dry relatively rapidly.…”
Section: Connection With the Surfacementioning
confidence: 99%
“…More importantly, we highlight that the sounding depths of the Cassini Radar/radiometer and of PWA‐MIP/HASI are similar: both instruments are sensitive to the composition and structure of, roughly, the first meter below the surface (Hamelin et al, ; Janssen et al, ). More specifically, in the case of PWA‐MIP/HASI it is a weighted volume average of the first meter with a weight decreasing with depth (for a more in‐depth discussion see Lethuillier, ).…”
Section: Titan's Subsurface Composition At the Hlsmentioning
confidence: 85%
“…Lastly, the permittivity probe PWA‐MIP/HASI on board the Huygens probe measured both the real and imaginary parts of the complex permittivity of the HLS in the extremely and very low frequency range. At 45 Hz (frequency for which the PWA‐MIP calibration is best), Hamelin et al () found εr=2.55±0.35 and εr′′ in the interval 0.2–0.8 for the first 11 min after the landing and εr=2.35±0.35 and εr′′ in the interval 0–0.1 after. These values are consistent with the ones previously published (Grard et al, ) but with more reliable error bars that account for uncertainties related to the probe's resting attitude on the surface.…”
Section: Titan's Subsurface Composition At the Hlsmentioning
confidence: 99%
See 2 more Smart Citations